The Religious Attitude of the Druze Towards Violence: A Study Based on Oral Sources: سلوك الدّروز الدّيني في استعمال العنف: دراسة تستند إلى المصادر الشّفهيّة - Abou Zaki, Said (Druze Studies Journal, 2024)
Since its rise in the 11th century AD, the Druze community has distinguished itself from its surroundings by its unique religious identity. This religious identity has given rise to social and political behaviors that have, over time, formed the collective character of the Druze. The Druze who upheld their religious identity were known as the ʿuqqāl, while others were called juhhāl. Historically, the ʿuqqāl have played vital social and political roles within their community, the most prominent of which has been preserving the Druze identity and the social and political behaviors arising from it. On the other hand, Druze history in the Levant—particularly in Lebanon—is marked by wars and armed uprisings, which have imparted a warlike character on the Druze that often overshadowed their other collective traits, despite their commitment to nonviolent principles. For these reasons, understanding the ʿuqqāl’s religious stance on the use of violence and their conduct in conflicts is of clear historical importance. This study investigates oral narratives about notable Druze ʿuqqāl in Lebanon during the past century, employing a rigorous methodology to reveal a consistent, comprehensive behavioral pattern grounded in fundamental religious principles. This behavior is characterized by a rejection of violence and aggression, an effort to prevent such acts, a condemnation of those who engage in them, and retribution where necessary. From a broader perspective, the ethical stance of religious adherents on violence is a contentious issue today and is receiving intense attention from research institutions and both governmental and non-governmental organizations, particularly given the global impact of religiously motivated violence. Consequently, this research carries significance beyond the Druze demographic presence in the Levant, as it offers principles and behavioral patterns that may contribute to fostering peaceful religious leadership on an international level.